Perancangan Sistem Keamanan Data pada Sistem Informasi Akademik Berbasis Web untuk Meningkatkan Integritas Data di MAS Alwashliyah Medan Deras - Muhammad Ihsan; Leni Marlina; Suheri (CV. Hawari, 2026)
A web-based Academic Information System assists schools in managing student, teacher, class, subject, grade, attendance, and academic report data. Nevertheless, web applications introduce security risks such as unauthorized access, unauthorized grade modification, input errors, data loss, and the absence of audit trails. This study aims to design a data security model for a web-based Academic Information System to improve data integrity at MAS Alwashliyah Medan Deras. The study applies a system development method using a waterfall model consisting of requirement analysis, system design, implementation, testing, and evaluation. The system was designed using PHP and MySQL by implementing authentication, password hashing, role-based access control, input validation, prepared statements, CSRF tokens, session timeout, audit logs, database constraints, and database backup. The testing data were generated from simulated academic data management scenarios involving five user roles, namely administrator, teacher, homeroom teacher, student, and principal. The black-box testing results show that all main modules operate according to the design. Basic security testing shows that invalid login attempts, unauthorized menu access, out-of-range grade input, simple SQL injection attempts, and forms without CSRF tokens were successfully rejected by the system. Therefore, the proposed system design can improve academic data integrity through access limitation, transaction validation, database relationship consistency, activity recording, and data recovery mechanisms.